TRATAMENTO ALTERNATIVO DE DEJETOS HUMANOS NA COMUNIDADE DE COQUILHO, ZONA RURAL DE SÃO LUIS-MA - Alencar, Marcelo Henrique Bandeira Costa de (2009)
In Brazil, the absence or deficiency of sanitation is a major cause of environmental degradation and proliferation of diseases accounting for an index is not as significant number of hospitalizations resulting in the increased spending públicos.A search for alternative technologies for waste treatment is a necessity for the country's development, which will be supplied when it is known to use effectively and with social equity, natural resources available. In this sense, the technology of dry toilet, a sanitary system for treatment of human waste using dry organic matter in the discharge instead of water, shows itself as a viable alternative considering its low cost and significant history of successful experiences in Brazil. This work has promoted the construction of a prototype single-chamber dry toilet bicompartimental composed of plates of the Community of plastocimento Die in rural São Luís / MA. Throughout the project implementation were held demonstrations, seminars and workshops that resulted in increasing the knowledge of the functioning of the bathroom dry from 2% to 90% within the group studied. After the workshops held in the Community; the perception by the population studied that the adoption of the bathroom would result in improving the health of the community increased from 20% to 60%. In the course of the project it was felt that the experience was successful and that the technique of dry toilet in the form of precast is feasible and may facilitate the replication of the experience in other rural communities in the state of Maranhao.